2021
DOI: 10.7717/peerj-cs.467
|View full text |Cite
|
Sign up to set email alerts
|

Stance detection with BERT embeddings for credibility analysis of information on social media

Abstract: The evolution of electronic media is a mixed blessing. Due to the easy access, low cost, and faster reach of the information, people search out and devour news from online social networks. In contrast, the increasing acceptance of social media reporting leads to the spread of fake news. This is a minacious problem that causes disputes and endangers the societal stability and harmony. Fake news spread has gained attention from researchers due to its vicious nature. proliferation of misinformation in all media, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…It could be because the CNN algorithm might extract local and global features very well from the vectors using the convolutional, the pooling, and the fully connected (dense) layers, which can maintain semantic context meaning on text data. This finding supports studies on sentiment analysis of a commodity review and stance detection for credibility analysis of information on social media conducted by [24], [25]. These studies showed that BERT embeddings and CNN obtained better results than single CNN that ignores relation contextual semantics on text.…”
Section: Discussionsupporting
confidence: 87%
“…It could be because the CNN algorithm might extract local and global features very well from the vectors using the convolutional, the pooling, and the fully connected (dense) layers, which can maintain semantic context meaning on text data. This finding supports studies on sentiment analysis of a commodity review and stance detection for credibility analysis of information on social media conducted by [24], [25]. These studies showed that BERT embeddings and CNN obtained better results than single CNN that ignores relation contextual semantics on text.…”
Section: Discussionsupporting
confidence: 87%
“…Stance polarity and intensity can be used as a feature to solve a multitude of task such as fake news detection (Karande et al , 2021), opinion polarization (Sirrianni et al , 2018), identifying outlier opinions (Arvapally et al , 2017) and rumor detection (Zubiaga et al , 2018). While these task can be performed using only stance polarity, a study on Cyber Argumentation shows that using stance polarity with the intensity of the relationship can improve the results of discussion analysis (Sirrianni et al , 2018).…”
Section: Related Workmentioning
confidence: 99%
“…Instead, to improve BERT performance on classification problem, several works have found success in combining BERT architecture with other deep learning method such as convolutional neural network (CNN), gated recurrent unit (GRU), long–short-term memory (LSTM) and Bi-LSTM. These research used hybrid BERT model for various tasks such as fake news detection (Karande et al , 2021), sentiment analysis (Zheng and Yang, 2019), identifying offensive speech (Safaya et al , 2020) and intent determination (He et al , 2019). In this research, they found that CNN method is able to outperform other deep-learning technique in improving the BERT performance.…”
Section: Introductionmentioning
confidence: 99%
“…we evaluated our models using Recall (R), Precision (P), and macro F1-measure. These machine and deep learning classifiers have shown competitive performance for several NLP tasks (Devlin et al, 2019;Kim, 2014;Hochreiter & Schmidhuber, 1997;Breiman, 2001;Kohavi, 1995;Bashir et al, 2019;Khan et al, 2021;Butt et al, 2021b;Karande et al, 2021;Ashraf et al, 2021;Ameer et al, 2021;Butt et al, 2021a).…”
Section: Benchmarksmentioning
confidence: 99%